Corporate social responsibility and customer-based brand equity - Vasiukov, Denis (2020)
Modern conditions for the development of market relations are characterized by a significant increase in globalization, which causes the liberalization of capital flows and significantly increases competition in world markets. In order to successfully operate and continue its development in this or that market, the company must actively fight for customer loyalty. The main objective of the study is to assess the influence of the company's CSR policy on customer loyalty to the «Activia» brand and increase the brand value for the consumer. The result showed that the main satisfaction level of the sample is quite high; almost 70% of respondents can recognize the «Activia» brand among other competing brands; and it was clear that the enterprise should pay more attention to CSR activities to persuading its customer based brand equity.